2022
DOI: 10.46747/cfp.6811e326
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound for evaluation of vaginal bleeding or abdominal pain in early pregnancy

Abstract: Objective To evaluate the use of point-of-care ultrasound (POCUS) for the assessment of patients experiencing first-trimester bleeding or abdominal pain by family physicians working in family medicine clinics following first-trimester POCUS training and certification. Design Multisite, retrospective chart review. Setting Two hospital-affiliated academic family medicine clinics in Toronto, Ont. Participants Twelve family physicians who completed a first-trimester POCUS training and certification course. Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Central to this evaluation is the ability to identify an IUP. Multiple studies have demonstrated POCUS to have excellent sensitivity and specificity for detecting an IUP 12–16 . In a large meta-analysis, the presence of an IUP by POCUS was able to rule out EP with a sensitivity of 99.3% and a negative likelihood ratio of 0.08 15 .…”
Section: Review Of the Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Central to this evaluation is the ability to identify an IUP. Multiple studies have demonstrated POCUS to have excellent sensitivity and specificity for detecting an IUP 12–16 . In a large meta-analysis, the presence of an IUP by POCUS was able to rule out EP with a sensitivity of 99.3% and a negative likelihood ratio of 0.08 15 .…”
Section: Review Of the Literaturementioning
confidence: 98%
“…Multiple studies have demonstrated POCUS to have excellent sensitivity and specificity for detecting an IUP. [12][13][14][15][16] In a large metaanalysis, the presence of an IUP by POCUS was able to rule out EP with a sensitivity of 99.3% and a negative likelihood ratio of 0.08. 15 In the absence of assisted fertilization, where the risk of heterotopic pregnancy is roughly 1:4000 to 1:30,000, the presence of an IUP essentially excludes the diagnosis of an EP.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To the group of this markers we can include antibodies to insulin, beta-cells of the pancreas, and insulin receptors [28] modern studies have shown, that the autoantibodies to islet pancreatic cells are specific markers of the autoimmunization in case of diabetes [29] it is proved that in the preclinical stage of diabetes we can see changes in the immune system, including production of the antibodies, that lead to destruction of the insulin-secreting cells of the pancreas. The action of the antibodies is realized in the autoimmune insula, which develops gradually; destruction of the endogenous insulin and desencibilisation of the receptors [30]. In the implementation of the autoimmune insula the most important role is played by macrophages, T-helpers, Tcytotoxic-suppressors and natural killer cells [31].…”
mentioning
confidence: 99%